2014
DOI: 10.1596/1813-9450-7014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Agricultural Input Landscape in Sub-Saharan Africa : Recent Plot, Household, and Community-Level Evidence

Abstract: Tor Vergata. Co-funding by the African Development Bank is gratefully acknowledged. It is part of a larger effort by the World Bank to provide open access to its research and make a contribution to development policy discussions around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
121
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(134 citation statements)
references
References 99 publications
(67 reference statements)
12
121
0
1
Order By: Relevance
“…This shows that although majority of the respondents applied fertilizer for trifoliate yam production, greater proportion of them applied it once before the crop was planted. From the foregoing, it can be inferred that fertilizer use appeared to be currently common in Nigeria and not as low as conventional wisdom suggests (Liverpool-Tassie et al, 2015;Sheaham and Barrett, 2014) but the rate of fertilizer use among Nigerian farmers may be considerably low probably due to scarcity and expensive nature of the products (both organic and inorganic fertilizers) in recent time.…”
Section: Types and Time Of Fertilizer Applicationmentioning
confidence: 92%
“…This shows that although majority of the respondents applied fertilizer for trifoliate yam production, greater proportion of them applied it once before the crop was planted. From the foregoing, it can be inferred that fertilizer use appeared to be currently common in Nigeria and not as low as conventional wisdom suggests (Liverpool-Tassie et al, 2015;Sheaham and Barrett, 2014) but the rate of fertilizer use among Nigerian farmers may be considerably low probably due to scarcity and expensive nature of the products (both organic and inorganic fertilizers) in recent time.…”
Section: Types and Time Of Fertilizer Applicationmentioning
confidence: 92%
“…This is largely due to private investment resulting from improved land management (Sheahan and Barrett 2014). For example, SSA farmers accounted for 86 % of the total agricultural investment 4 from 2005-07 (Lowder et al 2012).…”
Section: Slm Financingmentioning
confidence: 99%
“…Such growth has been driven by increasing consumer spending, investment in extraction of natural resources and infrastructure, a rapidly growing services sector, and increased agricultural productivity (World Bank 2014). SSA agricultural productivity has increased in the past few decades, thanks to farmer investments which has led to increased use of improved seeds and inorganic fertilizer (Sheahan and Barrett 2014). For example, Sheahan and Barrett (2014) found that in three of the six countries with a nationally representative household survey, farmers used an average of 57 kg/ha of fertilizer-a level which is much higher than the 13 kg/ha widely cited level, which is based on Food and Agriculture organization (FAO) data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is hardly any variation in female labor allocation across agricultural activities in Tanzania, Malawi and Nigeria. 25 This is likely linked to the low degree of mechanized land preparation in SSA, with the exception of Ethiopia (and to some extent also in Niger), where the use of draught animals is more widespread (Sheahan and Barrett, 2014).…”
mentioning
confidence: 99%